Outdoor Learning: Students’ Vocabulary Mastery in Higher Education - Munawir, Ahmad; Inayah, Nur; A, Marya; Huda, Nabila (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The objective of this report was to determine whether or not the utilization of Outdoor Learning techniques is beneficial in increasing students' vocabulary knowledge at IAI As'adiyah Sengkang's sixth semester of English instruction. This study uses a pre-Experimental design to attain its goal. This study's population comprised 13 students in their sixth semester of English education at IAI As'adiyah Sengkang. Purposive sampling was employed by the researcher. SPSS version 24 was used to analyze the data. The pre-test and post-test results demonstrated considerable improvement. The experimental post-test mean score of the students (78.25) was greater than the pre-test mean score of (53.85). Furthermore, the post-test t-test result was 0.00, which was less than (α) = 0.05 when examined with SPSS. As a result, it is concluded that Outdoor Learning is beneficial in improving the vocabulary mastery of sixth-semester English students IAI As'adiyah Sengkang.